Level of knowledge and misconceptions about brain concussion in Brazilian adults - De Araújo, Amanda Vitória Lacerda; Areza-Fegyveres, Renata; Guariglia, Carla Cristina; Ianof, Jéssica Natuline; Baratho, Regina Maria; Demario, José Luiz Carlos; Watanabe, Rafael Gustavo Sato; Anghinah, Renato (Arquivos de Neuro-Psiquiatria, 2021)
Background: Brain concussion (BC) is seen as a public health priority due to its high incidence and morbidity rate, among thousands of people around the world. There are needs for fast identification, accurate diagnosis and correct management in order to reduce the short and long-term problems relating to BC. Proper knowledge of BC in the population and among clinicians is a critical factor in achieving this. Objectives: To evaluate the level of self-reported BC knowledge and gaps/misconceptions, and to identify variables correlated with this level. Methods: A cross-sectional descriptive survey was performed. A Brain Concussion Knowledge Questionnaire (BCKQ) that had been created to capture data was widely distributed. Total scores, domain partial scores and percentages of correct and incorrect answers were calculated to ascertain the level of knowledge relating to BC. Results: The sample was formed by 1,247 Brazilian adults (age: 41.7±11.8 years). Partial scores of the BCKQ revealed the existence of poor knowledge and misconceptions in all domains of the questionnaire, especially regarding questions about recovery from and management of BC. Moderate correlations between BCKQ scores and professions (p=0.312; P=0.00) or previous brain concussion knowledge (p=0.489; P=0.00) were observed. In a multiple linear regression model, age, profession and sports practice were predictors of BC knowledge. Conclusion: This first study to analyze the level of BC knowledge in a sample of Brazilian adults suggests that poor knowledge and misconceptions are present. Thus, meaningful and useful information was provided by this study for developing health education programs about BC for the population in order to improve fast diagnosis and correct BC management.
Keywords: Brain Concussion; Cerebral Concussion; Health Care; Questionnaires